Analysis of an Individual’s Intention to Invest Using the Technology Acceptance Model (TAM) - Budisutiono, Clara Immanuella; Setyawan, Muhammad Dimas Arbi; Usman, Osly (Manunggal Halim Jaya, 2025)
Mutual funds are a means used to collect funds from investors, which are then managed and invested into a portfolio of securities by investment managers under the supervision of the Financial Services Authority (OJK). This investment instrument is also considered suitable for beginners, especially in assisting with efficient and effective financial planning. Currently, there are many mutual fund applications available to facilitate investors, one of which is the BIBIT application.This study aims to analyze how the features of the BIBIT application influence users' intention to invest through the application. The research was conducted by distributing online questionnaires via various social media platforms targeting BIBIT application users. The sampling technique used was purposive sampling. The collected data were then analyzed using PLS software for data processing.